SCS 5th Annual Conference. São Paulo, Brazil, 2022 - Pedro E. Alcaraz; Elena Marín-Cascales; Anthony J. Blazevich; Lucas A. Pereira; Valter P. Mercer; Túlio B. M. A. Moura; Victor Fernandes; Tomás T. Freitas; Irineu Loturco (Sports, 2023)
On behalf of the Strength and Conditioning Society (SCS) and the Nucleus of High Performance in Sport (NAR), we are pleased to present the abstracts of the SCS 5th Annual Conference, which, for the first time, took place outside of Europe. The event was held at NAR’s state-of-the-art facilities in São Paulo, Brazil, on 3–5 November 2022, and comprised several invited sessions from international and national speakers on a variety of topics related to strength and conditioning practices and their application to health, injury prevention and sports performance. These included strength training in high-performance sports and older adults, sleep and recovery in elite athletes, performance optimization of the female athlete, high-intensity interval training, velocity-based resistance training, and running and cycling biomechanics, among others. The Conference also included different practical workshops conducted by renowned academics and practitioners on post-competition recovery strategies, plyometric training, hamstring strain injuries in soccer, and resisted sprint training. Finally, the event disseminated up-to-date strength and conditioning research by providing practitioners and researchers with the opportunity to present their most recent findings. In this regard, all abstracts of the communications presented at the SCS 5th Annual Conference can be found in this Conference Report.